Students’ problem solving skill in nuclear physics course through NPIRL - Sri Hartini; Liliasari Liliasari; Parlindungan Sinaga (Momentum: Physics Education Journal, 2023)
This study aimed to describe students’ problem solving skill in nuclear physics course through the implementation of the Nuclear Physics Inquiry Remote Laboratory (NPIRL). This study employed a pre-experimental quantitative method. The research design was one group pretest-posttest design. The subject of the study was 14 physics students at a university in Banjarmasin, South Kalimantan. In selecting the research subjects, the researchers used purposive sampling technique. The instrument used was a problem-solving skills test in the form of an essay consisting of five questions, and each question consisted of six indicators in problem solving skill according to the Osborn-Parnes Creative Problem Solving (CPS). This research found that the N-gain of students' problem solving skill was 0.32 in the medium category. There are four indicators of problem-solving skills that are categorized as medium: objective finding, fact finding, problem finding and idea finding.  Two other low-category indicators are solution finding and acceptance finding. Based on these findings, it is concluded that students’ problem solving skill in nuclear physics course through NPIRL have increased.